Two sides of the coin: Feedback-driven landscape formation results in trade-off between establishment and resilience of marram grass - Solveig Höfer; Lissie de Groot; Nathan Scanlan; Eva Lansu; Max Rietkerk; Martin Wassen; Tjisse van der Heide; Valérie C. Reijers (Oecologia, 2025)
Habitat-modifying plants engineer biogeomorphic landscapes through self-reinforcing interactions with their physical environment, or so-called ‘biogeomorphic feedbacks’. Nevertheless, benefits can vary across a biogeomorphic landscape gradient and between plant-life stages. For instance, European marram grass forms dunes by trapping sediments which triggers plant growth, in turn promoting sediment trapping. Yet, by increasing dune height and vegetation cover, marram grass mitigates sediment dynamics, inhibiting sediment-growth feedbacks, which ultimately leads to its demise. However, little is known about how dune formation affects the growth and survival of marram grass at different life stages. Therefore, we performed a two-level field experiment testing the effect of position on marram grass across the biogeomorphological dune gradient (beach, foredune, backdune) on (i) the establishment success of juvenile transplants and (ii) the resilience of mature plants to disturbance by above-ground biomass removal, over one growing season. Although juvenile transplants grew similarly well across the dune gradient, significantly fewer beach transplants (67%) survived compared to the foredune- and backdune transplants. Conversely, survival of mature disturbed marram grass (100%) was unaffected, yet recovery was highest at the beach and significantly decreased across the dune gradient. We could link these opposing responses to habitat modification. In heavily modified dune habitats sediment stabilization aided juvenile establishment, whereas the high sediment dynamics of unmodified beaches facilitated adult resilience indicating dune formation invokes a trade-off between establishment and resilience. Our findings highlight the importance of assessing life stage-dependent differences in environmental requirements of habitat-modifying plants to understand population dynamics and landscape-forming processes.

Methanobactin and MmoD work in concert to act as the ‘copper‐switch’ in methanotrophs - Jeremy D. Semrau; Sheeja Jagadevan; Alan A. DiSpirito; Ashraf Khalifa; Julie Scanlan; Brandt H. Bergman; Brittani C. Freemeier; Bipin S. Baral; Nathan L. Bandow; Alexey Vorobev; Daniel H. Haft; Stéphane Vuilleumier; et al. (Environmental Microbiology, 2013)
Summary Biological oxidation of methane to methanol by aerobic bacteria is catalysed by two different enzymes, the cytoplasmic or soluble methane monooxygenase ( sMMO ) and the membrane‐bound or particulate methane monooxygenase ( pMMO ). Expression of MMOs is controlled by a ‘copper‐switch’, i.e. sMMO is only expressed at very low copper : biomass ratios, while pMMO expression increases as this ratio increases. Methanotrophs synthesize a chalkophore, methanobactin, for the binding and import of copper. Previous work suggested that methanobactin was formed from a polypeptide precursor. Here we report that deletion of the gene suspected to encode for this precursor, mbnA , in M ethylosinus trichosporium OB3 b, abolishes methanobactin production. Further, gene expression assays indicate that methanobactin, together with another polypeptide of previously unknown function, MmoD , play key roles in regulating expression of MMOs . Based on these data, we propose a general model explaining how expression of the MMO operons is regulated by copper, methanobactin and MmoD . The basis of the ‘copper‐switch’ is MmoD , and methanobactin amplifies the magnitude of the switch. Bioinformatic analysis of bacterial genomes indicates that the production of methanobactin‐like compounds is not confined to methanotrophs, suggesting that its use as a metal‐binding agent and/or role in gene regulation may be widespread in nature.